Peptídeos cíclicos de biomassa vegetal: características, diversidade, biossíntese e atividades biológicas - Picchi, Douglas Gatte [UNESP]; Altei, Wanessa Fernanda [UNESP]; Saito, Mônica Sue [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Cilli, Eduardo Maffud [UNESP] (Sociedade Brasileira de Química, 2009)
Natural peptides are outstanding as the most promising macromolecules in the search for new drugs, especially those of cyclic nature. The higher plants revealed a very peculiar composition of their cyclic peptides, which distinguish themselves by a head-to-tail cyclization. It is possible to define two groups of cyclic peptides from plant biomass. Those called in this review as Eucyclopeptides formed by 2-12 amino acid, and Cyclotides considered as circular polypeptides, composed of 29-37 amino acid that retain three disulfides bridges in an arrangement known as cyclic cystine knot. Searching for plant peptides should form into a subject for scientific research in the forefront of great importance for bioprospecting natural products macromolecular.
Cyclic peptide from plant biomass: chemical features and diversity, biosynthesis and biological activities
Keywords: cyclic peptides; eucyclopeptides; cyclotides